Konsep Mahabbah Kepada Allah: (Menggali Makna Cinta Persepektif Rabi’ah Al Adawiyah) - Anggraini, Silvi; Tesa Mukhlisa; Rizki Aulia Pratiwi; Ummi Latifah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
In the journey of life, humans need guidelines or foundations, such as religion or beliefs that recognize the existence of divine power. Every day, individuals are faced with the task of maintaining, improving and increasing the quality of faith and devotion to the Creator. To achieve this, several paths can be taken, one of which is through the world of Sufism or known as the mystical world. In pursuit of attainment in the mystical world, methods such as meditation or spiritual practice can be applied. The peak of experience in the mystical world is mahabbah or divine love, which is the highest level on the journey to Allah. In this article, the author investigates the theory of Divine love (mahabbah) from a female Sufi figure, Rabi'ah Adawiyah, who first expressed her affection for the Creator. This research adopts a library research approach. The approach method applied involves historical and philosophical dimensions. Data collection was carried out through documentation methods, and analysis was carried out using descriptive analysis methods. According to Rabi'ah, love is defined as a feeling of selfless love and without expecting reward or legal release in return. The focus is on the fulfillment of God's will and its perfection.